IMPROVING THE EFFICIENCY OF THE GINNING PROCESS TO ENHANCE FIBER QUALITY - Mirzaakbarov, Azizbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
It has been proven that the increase in the productivity of the gin machine necessarily occurs with an increase in the density of the raw material. However, with an increase in density, the productivity increases up to a certain limit, and then the productivity begins to decrease. In this article, the authors analyze the scientific work carried out to improve the quality of the fiber.